Clinical efficacy analysis of different therapeutic methods in patients with cesarean scar pregnancy - Yan Wu; Lei-Fang Sun; Ya-Nan Si; Xiao-Li Luan; Yong-Mei Gao (Elsevier, 2021)
Objective: The purpose of this study was to analyze the clinical efficacy of five therapeutic strategies in patients with CSP. Materials and methods: A total of 135 CSP patients were included and divided into five groups based on the treatment they received, including transvaginal resection (Group A), laparoscopic resection (Group B), uterine arterial embolization (UAE) combined with hysteroscopic curettage (Group C), UAE combined with uterine curettage (Group D), and hysteroscopic curettage (Group E). To investigate the clinical efficacy of these strategies, intraoperative bleeding, serum β-hCG levels and recovery time, menstruation recovery time, hormone levels at 1 month after treatment. Results: Patients in group A had the lowest postoperative serum β-hCG levels, and the shortest recovery times of both serum β-hCG and menstruation, followed by patients in group B. Group C and D had small amount of blood loss. The hospital stays and costs were low in group E. In addition, the sex hormone levels showed no significant difference among the five groups. Conclusion: Our results indicated that resection surgery and UAE have good curative effects, but high hospital costs in CSP treatment. The selection of an optimal treatment regimen for CSP should be carried out based on specific conditions of the patients.